Diffusion parameters of the extracellular space in human gliomas - Vargová, Lýdia; Homola, Ales; Zámecník, Josef; Tichý, Michal; Benes, Vladimír; Syková, Eva (Glia, 2003)
Tumor cell migration through the extracellular space (ECS) might be affected by its pore size and extracellular matrix molecule content. ECS volume fraction alpha (alpha = ECS volume/total tissue volume), tortuosity lambda (lambda(2) = free/apparent diffusion coefficient) and nonspecific uptake k' were studied by the real-time tetramethylammonium method in acute slices of human tissue. The diffusion parameters in temporal cortical tissue resected during surgical treatment of temporal lobe epilepsy (control) were compared with those in brain tumors. Subsequently, tumor slices were histopathologically classified according to the grading system of the World Health Organization (WHO), and proliferative activity was assessed. The average values of alpha, lambda, and k' in control cortex were 0.24, 1.55, and 3.66 x 10(-3)s(-1), respectively. Values of alpha, lambda, and k' in oligodendrogliomas did not significantly differ from controls. In pilocytic astrogliomas (WHO grade I) as well as in ependymomas (WHO grade II), alpha was significantly higher, while lambda and k' were unchanged. Higher values of alpha as well as lambda were found in low-grade diffuse astrocytomas (WHO grade II). In cellular regions of high-grade astrocytomas (WHO grade III and IV), alpha and lambda were further increased, and k' was significantly larger than in controls. Classic medulloblastomas (WHO grade IV) had an increased alpha, but not lambda or k', while in the desmoplastic type alpha and k' remained unchanged, but lambda was greatly increased. Tumor malignancy grade strongly corresponds to an increase in ECS volume, which is accompanied by a change in ECS structure manifested by an increase in diffusion barriers for small molecules.
Keywords: Analysis of Variance; dospělí; extracelulární prostor; gliom; Female; Infant; dítě; předškolní dítě; Adult; Iontophoresis; ženské pohlaví; Extracellular Space; Adolescent; nádory mozku; lidé; Glioma; iontoforéza; analýza rozptylu; Male; kojenec; Aged; Child, Preschool; Brain Neoplasms; mozková kůra; Cerebral Cortex; lidé středního věku; Child; senioři; mužské pohlaví; Middle Aged; mladiství; Humans